2005
DOI: 10.1007/s00702-005-0346-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of dopaminergic effects on skilled handwriting movements in Parkinson’s disease

Abstract: Patients with Parkinson's disease (PD) exhibit impairments in the execution of highly practiced and skilled motor actions such as handwriting. The analysis of kinematic aspects of handwriting movements has demonstrated that size, speed, acceleration and stroke duration are affected in PD. Although beneficial effects of dopaminergic therapy in regard to execution of movements have been reported, the effects of pharmacological therapy on these measures have not been examined in detail. The present study has comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 66 publications
3
83
0
1
Order By: Relevance
“…The results are in accordance with previous studies [6,9,11,13]. However, former studies have merely compared handwriting of PD patients and healthy controls and have not looked into different types of paper as possible cues for improving handwriting.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results are in accordance with previous studies [6,9,11,13]. However, former studies have merely compared handwriting of PD patients and healthy controls and have not looked into different types of paper as possible cues for improving handwriting.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our study confirmed that individuals with PD write slower than healthy controls [4,6,13]. The writing speed was not affected by writing on different types of paper in neither of groups.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the graphical deficits due to motor difficulties it can be found the presence of diseases such as Parkinson's Disease (PD) (Lange, 2006;Tucha, 2006;Longstaff, 2003); PD symptoms include bradykinesia, tremor, rigidity, reduced manual ability and loss of accuracy, which cause typical phenomena that can be classified using graphic gesture analysis and then related to the specific pathology (Tucha, 2006). In literature there are several studies finalized to the quantification of kinematic alterations in the graphic gesture in patients with PD.…”
Section: Assessment Of Motor Capabilitiesmentioning
confidence: 99%